2015
DOI: 10.4172/2155-6156.1000582
|View full text |Cite
|
Sign up to set email alerts
|

Morbid Obesity is Associated to Altered Fatty Acid Profile of Erythrocyte Membranes

Abstract: Background: Morbid obesity is a pathologic condition associated to an increased incidence of several chronic conditions associated to increased risk of mortality. Erythrocyte fatty acid composition has been candidate as a biomarker of oxidative stress and consequently on the rate of aging and ultimately lifespan. To our knowledge, no study has investigated the total spectrum of lipid composition of erythrocyte membranes from obese individuals. The aim of this study was to compare the fatty acid composition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 19 publications
0
11
1
Order By: Relevance
“…Intriguingly, del Genio et al . found lower contents of MUFAs, especially 16:1 and 18:1, and elevated levels of PUFAs within PHL in erythrocyte membranes from obese subjects, whereas our previous study of morbidly obese persons demonstrated an increase in serum MUFAs and a decrease in serum PUFAs . Also, Cordero et al .…”
Section: Lipid Alterations In Obesitycontrasting
confidence: 85%
See 4 more Smart Citations
“…Intriguingly, del Genio et al . found lower contents of MUFAs, especially 16:1 and 18:1, and elevated levels of PUFAs within PHL in erythrocyte membranes from obese subjects, whereas our previous study of morbidly obese persons demonstrated an increase in serum MUFAs and a decrease in serum PUFAs . Also, Cordero et al .…”
Section: Lipid Alterations In Obesitycontrasting
confidence: 85%
“…Evidence from many clinical studies points to potential role of dyslipidemia in pathogenesis of various conditions, such as obesity , cancer , interstitial fibrosis , coronary artery disease , liver steatosis , ophthalmic diseases , psychiatric disorders , Alzheimer's disease , atherosclerosis , polycystic ovary syndrome , chronic renal failure , birth defects , clinical depression , X‐linked adrenoleukodystrophy, Zellweger syndrome, neonatal adrenoleukodystrophy, infantile Refsum disease , diabetes and other diseases . Although not fully understood, the mechanisms explaining co‐occurrence of dyslipidemia, obesity and other comorbidities are with no doubt complex and multifaceted .…”
Section: Lipid Alterations In Obesitymentioning
confidence: 99%
See 3 more Smart Citations